The Progress of Mitophagy and Related Pathogenic Mechanisms of the Neurodegenerative Diseases and Tumor. (8th December 2015) - Song, Ying; Ding, Wei; Xiao, Yan; Lu, Kong-jun
Abstract : Mitochondrion, an organelle with two layers of membrane, is extremely vital to eukaryotic cell. Its major functions are energy center and apoptosis censor inside cell. The intactness of mitochondrial membrane is important to maintain its structure and function. Mitophagy is one kind of autophagy. In recent years, studies of mitochondria have shown that mitophagy is regulated by various factors and is an important regulation mechanism for organisms to maintain their normal state. In addition, abnormal mitophagy is closely related to several neurodegenerative diseases and tumor. However, the related signal pathway and its regulation mechanism still remain unclear. As a result, summarizing the progress of mitophagy and its related pathogenic mechanism not only helps to reveal the complicated molecular mechanism, but also helps to find a new target to treat the related diseases.